Effect of treatment variables on the super-fast drying method on the properties of dried low-density oil palm lumber (OPL) - Chen, Yuen Ling (2017)
“Super-Fast Drying” is a new oil palm wood (OPW) drying method which include drilling holes and hot pressing. From previous study, this technique could increase the drying rate of OPW with least defects. However, the method is still in preliminary phase. In this study, the best holing parameter for the low-density OPW (core of oil palm trunk) were verified. OPW were cut in the size of 300 x 50 x 20 mm, followed by holes drilling with the distance of 1.0 and 1.5 inch and hole diameter of 5, 7 and 9 mm. The specimen were hot pressed and oven dried. Mechanical and physical testing were carried out to determine the optimum parameters that show the best properties of super-fast dried OPW. From the findings, hole diameter results to significant effect on the properties, while hole distance does not. The optimum hole distance and hole diameter are 1.5 inch and 7mm, respectively.